Evaluation of 124I-JS001 for hPD1 immuno-PET imaging using sarcoma cell homografts in humanized mice - Haifeng Huang; Hua Zhu; Quan Xie; Xiaobin Tian; Xianteng Yang; Fan Feng; Qiyu Jiang; Xinan Sheng; Zhi Yang (Elsevier, 2020)
JS001 (toripalimab) is a humanized IgG monoclonal antibody which strongly inhibits programmed cell death protein 1 (PD1). In this study, we used a different iodine isotype (nat/124/125I) to label JS001 probes to target the human PD1 (hPD1) antigen. In vitro, the half maximal effective concentration (EC50) value of natI-JS001 did not significantly differ from that of JS001. The uptake of 125I-JS001 by activated T cells was 5.63 times higher than that by nonactivated T cells after 2 h of incubation. The binding affinity of 125I-JS001 to T cells of different lineages after phytohemagglutinin (PHA) stimulation reached 4.26 nmol/L. Humanized PD1 C57BL/6 mice bearing mouse sarcoma S180 cell tumors were validated for immuno-positron emission tomography (immuno-PET) imaging. Pathological staining was used to assess the expression of PD1 in tumor tissues. The homologous 124I-human IgG (124I-hIgG) group or blocking group was used as a control group. Immuno-PET imaging showed that the uptake in the tumor area of the 124I-JS001 group at different time points was significantly higher than that of the blocking group or the 124I-hIgG group in the humanized PD1 mouse model. Taken together, these results suggest that this radiotracer has potential for noninvasive monitoring and directing tumor-specific personalized immunotherapy in PD1-positive tumors.